2021
DOI: 10.15293/2658-6762.2103.07
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital learning technologies on functional and psychophysiological re-sponses of the organism: An analytical literature review

Abstract: Introduction. The ambiguous attitude of professionals in the field of education, students and their parents to modernization based on ICT, differences of regional educational systems in their provision with digital tools have heightened the need for research on the relevant problem associated with the implementation of the federal project called “Digital School”. The purpose of this study is to analyze the vectors of the impact of digital learning technologies on functional and psychophysiological state of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In 2015, it was shown that the proportion of adolescents with high blood pressure (BP) is higher among active Internet users aged 14-17 years (>2 hours per day) [8]. During a video game lasting longer than 24 min (which is lower than current hygienic standards), 42% of adolescents experience BP rise to a level of "hypertension" [9]. In the educational environment, including homework, the use of digital devices (computers, tablets, interactive whiteboards) exceeds 2 h per day.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, it was shown that the proportion of adolescents with high blood pressure (BP) is higher among active Internet users aged 14-17 years (>2 hours per day) [8]. During a video game lasting longer than 24 min (which is lower than current hygienic standards), 42% of adolescents experience BP rise to a level of "hypertension" [9]. In the educational environment, including homework, the use of digital devices (computers, tablets, interactive whiteboards) exceeds 2 h per day.…”
Section: Introductionmentioning
confidence: 99%